Analysis of Public Administration Challenges in the Development of Artificial Intelligence Industry 4.0 - Febiandini, Venni Vidya; Sony, Morina Shelvia (Pandawan Sejahtera Indonesia, 2023)
Technology is causing social and economic upheaval that is overturning the social order. Governments around the world have a lot of potential as a result of the widespread use of artificial intelligence (AI) in government. There are some difficulties in using AI in government. Meanwhile, the use of AI in government can increase public trust in it. The purpose of this article is to assess the level of AI preparedness in the Indonesian government, focusing on its application to public administration and e-government services. Conclusion The level of AI readiness in Indonesia is still low. In ASEAN, the use of AI is ranked fifth. Indonesia is ranked 57th out of 195 countries in the world. Novelty in this research is how BOT can survive amid the rapid development of Artificial Intelligence.